Analysis of the consumption of sports supplements in elite fencers according to sex and competitive level - Fernando Mata; Raúl Domínguez; Álvaro López-Samanes; Ángela Sánchez-Gómez; Pablo Jodra; Antonio J. Sánchez-Oliver (BMC, 2021)
Abstract Background The aim of this study was to analyze the consumption of sports supplements (SS) in competitive level fencers and compare differences based on sex and competitive level (international and national). Methods A total of 49 fencers (18 men and 31 women) of national (n = 16) and international (n = 33) level completed a questionnaire with questions about SS consumption and the possible repercussions on health and / or sports performance. The results were analyzed based on the different categorizations established by the Australian Institute of Sport (AIS), as well as by sex and level of competence to which the participants belonged to. Results 46.9% of fencers have consumed SS with the main motivation being performance improvement (34.2%). Medical doctors were the individuals who were more likely to advise men to consume SS (50.0% vs 5.6%; OR = 3.29 [1.50-7.20]). Friends were most likely to advise women (38.9% vs 8.3%; OR = 1.75 [1.05-2.93]). The most consumed SS were sport drinks (44.9%), vitamin C (43.4%), sport bars (38.8%), and caffeine (28.6%). In regards to the SS categories, it was observed differences in the interaction level·sex in medical supplements (p = 0.017). In addition, there was a higher prevalence of whey protein consumption in women (25.8% vs 0%; p = 0.020) and iron consumption in men (33% vs 6.5%; p = 0.039). Conclusions The prevalence of SS use in fencers is within the values previously reported in athletes of the same competitive level. There were no differences by sex and competitive level in the total consumption of SS, nor in each of the groups of level of evidence, being sport drinks, bars and caffeine the most consumed SS.